Prognostic value of pet/ct determined sarcopenia inpatients with resected ampullary carcinoma - ÖZGÜVEN, SALİH; ARIKAN, RUKİYE (My University, 2022)
Objectives: Our aim is to investigate the prognostic value and effect on chemotherapy toxicity of pre-treatment sarcopenia determined with positron emission tomography/computerized tomography(PET/CT) in patients with ampullary carcinoma. Methods: Characteristics of patients retrieved retrospectively. Skeletal muscle area(SMA) measurement of the muscle at L3 vertebra level was evaluated for each patient from their PET/CT scan taken at the time of diagnosis. The sex-specific cut-off levels for determining sarcopenia were <38.5 cm2/m2 for females and <52.4 cm2/m2 for males. Association between oncological and radiological data was analyzed. Results: A total of 90 patients included in the study. Median age at diagnosis was 62(range: 44-77). Half of the patients were sarcopenic. Pre-treatment sarcopenia was determined as an independent variable predicting survival for both disease-free-survival(DFS) and overall survival(OS). Sarcopenic patients had statistically significant shorter OS(67.2 months for non-sarcopenic patients vs 53.2 months for sarcopenic patients, 95%CI:63.6-70.9, p<0.001), and a trend for shorter DFS(48 months for non-sarcopenic patients vs 36.8 months for sarcopenic patients, 95%CI:20.3-53.4, p=0.95) was also determined. On the other hand, chemotherapy related toxicity has also seen more in sarcopenic patients. Conclusion: Detecting the presence of pre-treatment sarcopenia may enable clinicians to predict the patient group with low survival and high probability of treatment toxicity. In order to protect this group of patients from toxicity, pretreatment sarcopenia measurement should be applied in routine practice and should guide treatment plan.
Keywords: Ampullary carcinoma; sarcopenia; toxicity; survival